2010
DOI: 10.1590/s0100-69162010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Perda de carga localizada em gotejadores integrados em tubos de polietileno

Abstract: Este trabalho foi desenvolvido para analisar as perdas de carga localizadas em gotejadores coaxiais integrados em tubos de polietileno. A perda de carga para diferentes vazões foi determinada em quatro modelos de tubos gotejadores, com sete repetições. Para cada vazão, a perda de carga localizada foi calculada pela diferença entre a perda de carga no tubo com emissor e a perda de carga contínua no tubo uniforme, estimada pela equação de Darcy-Weisbach. Aproximações matemáticas foram sugeridas para calcular a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
2
11
0
10
Order By: Relevance
“…The total head loss in the emitter pipe was quantified as a function of the flow rate using a potential type model (Equation 5) as proposed by Gomes et al (2010). In order to obtain the local head loss on the emitter it is necessary to estimate the distributed head loss in the pipe, and for this we used the universal equation with the coefficient f determined by the Blasius equation (Equation 6), with coefficients proposed by Rettore Neto et al (2009) Table 3 shows the maximum and minimum values for each emitter pipe model studied on variables observed in the study, flow rate, temperature, total head loss in the emitter pipe, and variables calculated, mean velocity at uniform pipe section, viscosity, Reynolds number, Darcy friction factor, distributed head loss in the pipe and local head loss on the emitter .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total head loss in the emitter pipe was quantified as a function of the flow rate using a potential type model (Equation 5) as proposed by Gomes et al (2010). In order to obtain the local head loss on the emitter it is necessary to estimate the distributed head loss in the pipe, and for this we used the universal equation with the coefficient f determined by the Blasius equation (Equation 6), with coefficients proposed by Rettore Neto et al (2009) Table 3 shows the maximum and minimum values for each emitter pipe model studied on variables observed in the study, flow rate, temperature, total head loss in the emitter pipe, and variables calculated, mean velocity at uniform pipe section, viscosity, Reynolds number, Darcy friction factor, distributed head loss in the pipe and local head loss on the emitter .…”
Section: Methodsmentioning
confidence: 99%
“…In studies carried out by Bagarello et al (1997), Gomes et al (2010), Provenzano et al (2005) and Rettore Neto et al (2009) it was evidenced that for conditions where Reynolds number (Re) is greater than 10,000 the viscous forces become negligible, thus, the obstruction becomes the main cause of the local head loss. In order to evaluate the head loss as a function of the obstruction, Bagarello et al (1997) developed an exponential equation (Equation 2) based on the Obstruction Index (Equation 3).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing results from both methods, gave a value of 19.48%, which seems to represent a significant difference caused by neglecting local head loss effects. Depending on the type of dripper, GOMES et al (2010) reported that maximum lateral length could be overestimated by around 25.7% (NPC drippers) and 9.5% (PC drippers) when local head losses were neglected. Based on the results shown in Table 8, the maximum lateral length was overestimated by around 19.48% (emitting pipe 4 -PC dripper) and 16.48% (emitting pipe 9 -NPC dripper) when local head losses were neglected.…”
Section: Applying the Developed Model On Designing Late Ralsmentioning
confidence: 99%
“…Although drip irrigation systems have several advantages over other irrigation systems, the ideal water distribution along the lateral cannot be achieved due to variations in emitter discharge. These variations are influenced by operating pressure and water temperature (DOGAN & KIRNAK, 2010;BORSSOI et al, 2012); emitter manufacturing process; emitter clogging (TARCHITZKY et al, 2013;ZHOU et al, 2013) and pressure variations caused by slope (ZHU et al, 2010) and friction losses (RETTORE NETO et al, 2009;GOMES et al, 2010;VEKARIYA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Gomes et al (2010) os fabricantes disponibilizam ao mercado diversos modelos de emissores/conectores, que em geral, não apresentam as características relacionadas às dimensões e a perda de carga localizada provocada por eles no escoamento através da tubulação. A determinação das perdas de carga localizadas é mais complexa de se obter, além de apresentar variações significativas entre os modelos disponíveis no mercado.…”
Section: Introductionunclassified